Transformasi Budidaya Salak Pondoh Menuju Agrowisata Berkelanjutan : Studi Historis Dinamika Ekonomi dan Sosial Desa Wisata Garongan - Fiya Zulfa Nabila; Numassikku Khoirinnillah Turkan; Ahmad Ardiyanto; Yudha Trishananto (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyse changes in the function of salak pondoh cultivation, specifically in the village of Garongan, which was originally only an agricultural commodity but has now become the foundation of sustainable agrotourism, while also examining the role and empowerment of local communities in addressing economic challenges and conservation. Historically, there was a surge in market prices in the 1990s, which caused unstable price fluctuations. The methods used included qualitative methods such as in-depth interviews, field observations, and literature reviews, with primary sources obtained from interviews with a salak farmer named Pak Pariyoto and Village chief. The results of the study show that the transformation of salak pondoh farming into an educational tourist destination has expanded the resource sector beyond economics to include social and tourism sectors. The conservation of salak plantations depends on the integration of cultural practices such as oral traditions that require the active involvement of the community. The collaboration between farmers and the tourism industry has created better marketing opportunities and enriched the cultural heritage and welfare of the village community. Overall, the results of this research confirm that the enthusiasm and creativity of local farmers have transformed market challenges into sustainable opportunities, making salak the foundation of the economy and tourism identity of Garongan Village.